Higher mortality in acute coronary syndrome patients without standard modifiable risk factors: Results from a global meta-analysis of 1, 285, 722 patients. (15th January 2023) - Kong, Gwyneth; Chin, Yip Han; Chong, Bryan; Goh, Rachel Sze Jen; Lim, Oliver Zi Hern; Ng, Cheng Han; Muthiah, Mark; Foo, Roger; Vernon, Stephen T.; Loh, Poay Huan; Chan, Mark Y.; Chew, Nicholas W.S.; et al.
Abstract: Background: Standard modifiable cardiovascular risk factors (SMuRF), comprising diabetes, hyperlipidemia, hypertension, and smoking, are used for risk stratification in acute coronary syndrome (ACS). Recent studies showed an increasing proportion of SMuRF-less ACS patients. Methods: Embase, Medline and Pubmed were searched for studies comparing SMuRF-less and SMuRF patients with first presentation of ACS. We conducted single-arm analyses to determine the proportion of SMuRF-less patients in the ACS cohort, and compared the clinical presentation and outcomes of these patients. Results: Of 1, 285, 722 patients from 15 studies, 11.56% were SMuRF-less. A total of 7.44% of non-ST-segment-elevation ACS patients and 12.87% of ST-segment-elevation myocardial infarction (STEMI) patients were SMuRF-less. The proportion of SMuRF-less patients presenting with STEMI (60.71%) tended to be higher than those with SMuRFs (49.21%). Despite lower body mass index and fewer comorbidities such as chronic kidney disease, peripheral arterial disease, stroke and heart failure, SMuRF-less patients had increased in-hospital mortality (RR:1.57, 95%CI:1.38 to 1.80) and cardiogenic shock (RR:1.39, 95%CI:1.18 to 1.65), but lower risk of heart failure (RR:0.91, 95%CI:0.83 to 0.99). On discharge, SMuRF-less patients were prescribed less statins (RR:0.93, 95%CI:0.91 to 0.95), beta-blockers (RR:0.94, 95%CI:0.92 to 0.96), P2Y12 inhibitors (RR: 0.98, 95%CI: 0.96 to 0.99), and angiotensin-converting-enzyme inhibitor or angiotensin-receptor blocker (RR:0.92, 95%CI:0.75 to 0.91). Conclusion: In this study level meta-analysis, SMuRF-less ACS patients demonstrate higher mortality compared with patients with at least one traditional atherosclerotic risk factor. Underuse of guideline-directed medical therapy amongst SMuRF-less patients is concerning. Unraveling novel risk factors amongst SMuRF-less individuals is the next important step. Summary: Standard modifiable cardiovascular risk factors (SMuRF), comprising diabetes mellitus, hyperlipidemia, hypertension, and smoking, are often used for risk stratification in acute coronary syndrome (ACS). Recent studies showed an increasing proportion of SMuRF-less ACS patients. Of 1, 285, 722 ACS patients, 11.56% were SMuRF-less. Despite lower body mass index and fewer comorbidities, SMuRF-less patients had increased in-hospital mortality and cardiogenic shock. However, despite worse outcomes, SMuRF-less patients were prescribed less guideline-directed medical therapies on discharge. Graphical abstract: Central Illustration. The Overall Proportion, Clinical Presentation, and Outcomes of SMuRF-less Patients with ACS. Unlabelled Image Highlights: Standard modifiable risk factors (SMuRF - diabetes, hyperlipidemia, hypertension, smoking) are used for stratification in ACS. Recent studies have showed an increasing proportion of SMuRF-less ACS patients. Of 1, 285, 722 ACS patients, 11.56% were SMuRF-less. Despite fewer comorbidities, SMuRF-less patients had increased in-hospital mortality and cardiogenic shock. SMuRF-less patients were prescribed less guideline-directed medical therapies on discharge.